The Effects of Artificial vs. Natural Rearing on Growth Performance, Thyroid Hormone Levels, Locomotor Activity, Carcass Traits and Meat Quality Characteristics in Chios Lambs - Panagiotis Simitzis; Georgia Alexopoulou; Eftychis Karampekos; Konstantina Linardopoulou; Anargyros Rigakis; Niki Stamelou; Michael Goliomytis; Iosif Bizelis; Ioannis Bossis (Animals)
Artificial rearing (AR) of lambs is nowadays a common practice in Mediterranean dairy sheep production systems to enhance the milk available for cheese or yoghurt manufacturing. The sufficient growth of lambs in an AR system is vital for the economic success of dairy sheep farms. However, AR is often associated with negative impacts on the performance and physiology of lambs. Greece is one of the major producers of ovine milk; nevertheless, data concerning the effects of artificial rearing in lambs of Greek autochthonous breeds are not available. Therefore, the present study aimed to examine the influence of artificial rearing on growth performance, thyroid hormone levels, locomotor activity, carcass traits and meat quality characteristics in lambs of the Chios breed, which is one of the most well-known Greek dairy sheep breeds. Twenty-one singleton male lambs were assigned into two feeding regimes; natural rearing NR (n = 11) and AR (n = 10). The lambs’ behavior was continuously videotaped until weaning, and their standing percentage was recorded as an activity index. Blood samples were collected from the jugular vein of lambs on days 3, 10, 17 and 40 after birth to assess thyroid hormone levels. The body weight of lambs was also recorded weekly. At the age of 45 days, lambs were fasted for 12 h, weighed and slaughtered. The weights of the carcass and internal organs were measured, while samples of the longissimus dorsi muscle were used for the determination of meat pH, color, water holding capacity, shear force and oxidative stability values. As indicated, body weight (kg) at birth was greater in NR vs. AR group and this difference was maintained till day 35 (p < 0.05), although body gain (kg) was generally not significantly different between NR and AR lambs, with the exception of the first week, when NR showed a greater value compared with the AR lambs (p < 0.001). On day 42, no significant differences between lamb groups for body weight were observed. Levels for triiodothyronine (T3), thyroxine (T4) and the free form of T3 (FT3) were greater, whereas the standing percentage was lower in NR compared with AR lambs (p < 0.05). The feeding regime of lambs did not affect carcass traits, internal organ and fat tissue weights, except for cold carcass yield which was greater in AR vs. NR lambs. No significant differences were observed between the two lamb groups in meat quality characteristics, such as pH, color, water holding capacity and shear force values, although MDA content was decreased in AR lambs indicating an improved oxidative stability. In conclusion, artificial rearing appears to be a feasible strategy for Chios lamb meat production, since it does not negatively influence carcass traits and meat quality characteristics, while a positive effect in meat oxidative stability is observed.